Extracellular Vesicles in Cardiovascular Diseases: Diagnosis and Therapy - Zhang, Xiaojing; Wu, Yuping; Cheng, Qifa; Bai, Liyang; Huang, Shuqiang; Gao, Jun (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs) are the leading cause of global mortality. Therapy of CVDs is still a great challenge since many advanced therapies have been developed. Multiple cell types produce nano-sized extracellular vesicles (EVs), including cardiovascular system-related cells and stem cells. Compelling evidence reveals that EVs are associated with the pathophysiological processes of CVDs. Recently researches focus on the clinical transformation in EVs-based diagnosis, prognosis, therapies, and drug delivery systems. In this review, we firstly discuss the current knowledge about the biophysical properties and biological components of EVs. Secondly, we will focus on the functions of EVs on CVDs, and outline the latest advances of EVs as prognostic and diagnostic biomarkers, and therapeutic agents. Finally, we will introduce the specific application of EVs as a novel drug delivery system and its application in CVDs therapy. Specific attention will be paid to summarize the perspectives, challenges, and applications on EVs’ clinical and industrial transformation.